A Methodology of Collaborative Performance Measurement for Manufacturing Collaboration - Jung, Jae-Yoon; Lee, Jinsung; Jung, Jihwan; Kim, Sang-Kuk; Shin, Dongmin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
The development of effective performance measures is requisite to effectively maintain successful collaboration. In our paper, a methodology of collaborative performance measures is presented to evaluate the overall performance of a collaboration case which multiple manufacturing partners participate in. The collaboration partners first define collaborative key performance indicators (cKPI), and they then measure the cKPIs and calculate the synthetic performance from the cKPI values to evaluate the result of the collaboration case. For the methodology, a two-folded desirability function is developed based on the logistic sigmoid function to measure different scales of cKPIs. The proposed methodology can provide a quantitative way of measuring collaborative performance to effectively manage collaboration among partners and continuously improve their performance.